2007
DOI: 10.1614/wt-07-009.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesosulfuron Rate and Formulation on Wild Oat (Avena Fatua) Control and Malt Barley Tolerance

Abstract: Experiments were conducted in 2005 and 2006 near Huntley, Montana to evaluate two formulations of mesosulfuron-methyl for the control of wild oat in malt barley. The two formulations differed due to the amount of safener, mefenpyr-diethyl, that each contained. Formulation 1 and 2 contained mesosulfuron-methyl and mefenpyr-diethyl at a 1 : 2 and 1 : 6 ratio, respectively. The two formulations were applied alone at two rates or in combination with other small grain herbicides that are typically used for broadlea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Wheat herbicides (sulfosulfuron and mesosulfuron) used for control of Phalaris minor in wheat are not safe for barley (King, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat herbicides (sulfosulfuron and mesosulfuron) used for control of Phalaris minor in wheat are not safe for barley (King, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they found that yield losses decreased when crop seeding rate was increased to 280 plants m À2 . In addition, lack of wild oat control reduced both harvest efficiency and grain quality of crops (King, 2007). This is a particularly important aspect in barley production, because the trading standard set by industry may prescribe substantial penalties in final price received by farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Both AOPPs and sulphonylureas are typically co‐formulated with safeners for use in the field (Tal et al. , 1993; King, 2007). In the current study, we have concentrated on the AOPP herbicide fenoxaprop ethyl and its partner safeners fenchlorazole ethyl and mefenpyr diethyl (Figure 1).…”
Section: Introductionmentioning
confidence: 99%